The historical understanding of the Old Testament in South Africa: Colenso, Le Roux and beyond - Hendrik L. Bosman (Verbum et Ecclesia, 2013)
Isaiah Berlin quoted Archilochus to distinguish between two styles of academic reasoning that, to some extent, summarises the transition of historiography from Modernism to Postmodernism: The fox knows many things but the hedgehog knows one big thing. The modernistic master narratives of the first half of the 20th century (quests for the centre of the Old Testament etc.) were in obvious decline during the second half of the 20th century and, triggered by the Annales school of historiography social scientific methods, were incorporated into the study of ancient Israel. Historiography became less of an art that depended on an informed imagination and more like a science that presupposed empirical or social scientific research and a multidisciplinary approach to describe and explain the past. Against this backdrop, the historical understanding of the Old Testament in South Africa was discussed, starting with one of its oldest exponents, Bishop J.W. Colenso (disproving the chronological priority of the E source, rejecting the truth proving function of archaeology and interpreting biblical texts within the historical context of its writing), and concluding with the current chair of the Old Testament Society of South Africa, Prof J.H. le Roux (influenced by Old Testament scholars such as G. von Rad and E. Otto and historiographers such as E. Troeltsch and R.G. Collingwood). The methodological principles of historiography suggested by Troeltsch (criticism, analogy and correlation) were adapted to describe and explain some trends in South African Old Testament historiography that go beyond a superficial division between maximalists and minimalists.